PENGARUH LATIHAN SINGLE LEG BOUND TERHADAP POWER OTOT TUNGKAI PADA CLUB BULUTANGKIS PB KURNIA JAYA PEKANBARU - Dwi Cahyo Putra; Zainur Zainur; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstark: The problem in this research is that when making a smash jump many shuttles are connected to the net, and if the net shuttle often hits the lip of the net and rarely goes into the field, the purpose of this research to determine the muscle strength of the athlete's foot. The form of this research is (one group pretest-postest design) with the population of the PB Kurnia Jaya Pekanbaru team. The data in this research was the full population of 10 people. The instrument used in this research was the use of the vertical jump test which aims to assess the effect of single leg training. Based on the analysis of the normality test on the independent variable (X), it produces a LoMax of 0.171 and an L table of 0.258, which means that LoMax <L table. While the dependent variable (Y) produces a LoMax of 0.167 and an L table of 0.258. This means that LoMax <L The data table is normally distributed. When testing the hypothesis on the t-distribution, it can be concluded that between the x variable and the y variable the value of t = 3,250 is obtained, then tcount> ttable (3,250)> (1,833), then Ha accepted, in other words, there is an effect of ankle bone training on limb muscle strength at the badminton club PB Kurnia Jaya Pekanbaru.Key Words: One Leg Bound Exercise, Leg Muscle Strength, Badminton